Інженерні та оборонні споруди на Дніпрі періоду російсько-турецької війни 1736-1739 рр. - Шпитальов, Г. (Чорноморська минувшина, 2016)
У статті розглядаються інженерні та оборонні споруди, побудовані на берегах Дніпра в період російсько-турецької війни 1736-1739 рр. Йдеться, насамперед, про споруди й укріплення, котрі були зведені на дніпровських порогах для спуску транспортних і бойових човнів Дніпровської військової флотилії, а також про укріплені гавані в нижній течії Дніпра, пристосовані для стоянок човнярських загонів. Визначено основні етапи будівництва цих споруд, їх розташування і призначення. Показано місце цих споруд на театрі війни, а також їх стратегічне значення. Дослідження побудовано на опублікованих документах і матеріалах російської армії і флоту періоду правління імператриці Анни Іоаннівни. The article deals with engineering and fortifications built on the banks of the Dnieper during the Russian-Turkish war 1736-1739 years. It is primarily about buildings and fortifications that were built on the Dnieper thresholds for launching boats and military transport Dnieper Flotilla, as well as fortified harbor in the lower reaches of the Dnieper, adapted for Boat parking units. The main stages of construction of these facilities, their location and purpose. The place of these buildings in the theater of war, as well as their strategic importance. In the militaryhistorical literature this question has not received special attention of researchers. Today in Russia and Ukraine, the topic has a narrow circle of specialists. The aim of this study is the total reconstruction of the main stages of construction and use of buildings erected on the banks of the Dnieper to the needs of the Russian army and navy during the years 1736-1738. Source base of this study are published written sources. A special place is occupied by documentary materials, whose appearance is due to the needs and requirements of the central authorities of the Russian Empire. Among them - the imperial edicts and the Senate and the Admiralty Board resolutions, which were published during the XIX ctolittya. Unfortunately, unpublished documents still ignored researchers. Mostly they are kept in the archives of the Russian Federation. Thus, our study is not the final product in developing the theme, but a reconstruction, which provides guidance for new discoveries. During the work we have been able to perform the following research objectives: 1) to show the reasons for the construction of fortifications on the banks of the Dnieper in the late 30s of the eighteenth century; 2) to identify the main stages of construction of these facilities, their location and destination; 3) determine the location of the Dnieper line of fortifications in the plans of the Russian government and the high command during the Russian-Turkish War, 1736-1739; 4) specify the functions and activities of the garrisons of the Dnieper fortifications. The first fortifications were built on the Dnieper River in the summer of 1736 during a campaign Dnieper Army Field Marshal H.Miniha in Crimea. Based on the plans for the 1737 campaign, during which Russian troops were to seize the fortress Ochakov, the government decided to create a "Dnipro expedition" for immediate construction of river flotilla, which was made up of undersized fighting, trucks and utility vehicles. Ready to ship with military cargo were lower on the Dnieper and in the Dnieper-Bug estuary. During the Russian-Turkish war of 1736-1739 years on the Dnieper River was built a system engineering and fortifications. They were involved in the construction of significant human resources, first of all, it Dnieper army soldiers. In terms of military expediency of construction of these facilities were fully justified. The development of the Ukrainian town planning the middle XVIII century building Dnipro lines are not affected. This was for three reasons. First, the fortifications were built in the desert. Secondly, part of the fortifications was partially demolished before the evacuation of military commands. Third, even surviving objects could not continue to operate due to the fact that according Byelґradskoho peace treaty in 1739 the Russians had no right to renew. В статье рассматриваются инженерные и оборонительные сооружения, построенные на берегах Днепра в период русско-турецкой войны 1736-1739 годов. Речь идет о сооружениях и укреплениях, которые были возведены на днепровских порогах для спуска транспортных и боевых лодок Днепровской военной флотилии, а также о укрепленных гаванях в нижнем течении Днепра, приспособленных для стоянок лодочных отрядов. В военно- исторической литературе этот вопрос не получил особого внимания исследователей. На сегодня как в России, так и в Украине, данной темой владеет узкий круг специалистов. Целью данного исследования является общая реконструкция основных этапов строительства и использования сооружений, возведенных на берегах Днепра для нужд российской армии и флота на протяжении 1736-1738 годов. Источниками для данного исследования являются опубликованные документы и материалы российской армии и флота периода правления императрицы Анны Иоанновны. Особое место занимают документальные материалы, появление которых обусловлено потребностями и требованиями центральных органов власти Российской империи. Среди них - императорские и сенатские указы, а также постановления Адмиралтейств-коллегии, которые были опубликованы в течение XIX века. К сожалению, неопубликованные документы всё ещё остаются вне поля зрения исследователей. В основном они хранятся в архивах Российской Федерации. Поэтому наше исследование не является конечным продуктом в разработке темы, а представляет собой реконструкцию, которая дает ориентиры для новых открытий. В ходе работы нам удалось выполнить следующие исследовательские задачи: 1) показать причины строительства укреплений на берегах Днепра в конце 30-х годов ХVIII века; 2) определить основные этапы строительства этих сооружений, их расположение и назначение; 3) определить место Днепровской линии укреплений в планах российского правительства и высшего командования во время в русско-турецкой войны 1736-1739 годов; 4) конкретизировать функции и деятельность гарнизонов днепровских укреплений. Первые оборонительные сооружения на Днепре были сведены летом 1736 года во время похода Днепровской армии генерал-фельдмаршала Х.Миниха на Крым. Исходя из планов на кампанию 1737 года, в ходе которой российские войска должны овладеть крепостью Очаков, правительство решило создать “Днепровскую экспедицию” для срочного строительства речной флотилии, которая должна состоять из маломерных боевых, транспортных и вспомогательных судов. Готовые судна с военным грузом должны были спускатся в Днепр и далее в Днепровско-Бугский лиман. За период русско-турецкой войны 1736-1739 годов на Днепре было построено целую систему инженерных и оборонительных сооружений. На их строительстве было задействовано значительные трудовые ресурсы, в первую очередь, это солдаты Днепровской армии. С точки зрения военной целесообразности строительство этих сооружений было вполне оправданным. На развитие украинского градостроительства середины XVIII века крепости Днепровской линии не повлияли. На это было три причины. Во-первых, укрепления были построены в пустынной местности. Во-вторых, часть укреплений была частично снесена перед эвакуацией военных команд. В-третьих, даже уцелевшие объекты не могли дальше эксплуатироваться в связи с тем, что согласно Белґрадського мирного договора 1739 российская сторона не имела права их отстраивать.